Activation and desensitization of the olfactory cAMP-gated transduction channel: identification of functional modules - Waldeck, Clemens zu; Vocke, Kerstin; Ungerer, Nicole; Frings, Stephan; Möhrlen, Frank (The journal of general physiology, 2009)
Olfactory receptor neurons respond to odor stimulation with a receptor potential that results from the successive activation of cyclic AMP (cAMP)-gated, Ca2+-permeable channels and Ca2+-activated chloride channels. The cAMP-gated channels open at micromolar concentrations of their ligand and are subject to a Ca2+-dependent feedback inhibition by calmodulin. Attempts to understand the operation of these channels have been hampered by the fact that the channel protein is composed of three different subunits, CNGA2, CNGA4, and CNGB1b. Here, we explore the individual role that each subunit plays in the gating process. Using site-directed mutagenesis and patch clamp analysis, we identify three functional modules that govern channel operation: a module that opens the channel, a module that stabilizes the open state at low cAMP concentrations, and a module that mediates rapid Ca2+-dependent feedback inhibition. Each subunit could be assigned to one of these functions that, together, define the gating logic of the olfactory transduction channel.